2013
DOI: 10.1186/1753-2000-7-40
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of online administered parental strengths and difficulties questionnaire (SDQ), and normative data based on combined online and paper-and-pencil administration

Abstract: ObjectiveTo examine the psychometric properties of the online administered parental version of the Strength and Difficulties Questionnaire (SDQ), and to provide parental norms from a nationwide Swedish sample.MethodsA total of 1443 parents from of a national probability sample of 2800 children aged 10-13 years completed the SDQ online or as usual (i.e., using paper-and-pencil).ResultsThe SDQ subscales obtained from the online administration showed high internal consistency (polychoric ordinal alpha), and confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
79
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(90 citation statements)
references
References 38 publications
9
79
1
1
Order By: Relevance
“…SDQ has shown good psychometric properties indicated by satisfying internal consistency, test-retest stability and inter-rater agreement, as well as proper criterion validity when compared with other measures of psychopathology [43]. The proposed factor structure has also been replicated and confirmed with a Swedish population [44,45]. The subscales capturing peer problems, hyperactivity-inattention, pro-social behaviors as well as the total sum score were used in the current study.…”
Section: Strength and Difficulties Questionnaire (Sdq)mentioning
confidence: 97%
“…SDQ has shown good psychometric properties indicated by satisfying internal consistency, test-retest stability and inter-rater agreement, as well as proper criterion validity when compared with other measures of psychopathology [43]. The proposed factor structure has also been replicated and confirmed with a Swedish population [44,45]. The subscales capturing peer problems, hyperactivity-inattention, pro-social behaviors as well as the total sum score were used in the current study.…”
Section: Strength and Difficulties Questionnaire (Sdq)mentioning
confidence: 97%
“….06 Prosocial 8 (7-9) 9 (8-10) 8 (8-9) 9.5 (8.5-10) 9 (8.5-10) 9 (7)(8)(9) .02* Total difficulties score 8 (5-12) 6 (4-8) 6 (4-11) 6 (4-10.5) 6.5 (4.5-11) 9 (7)(8)(9)(10)(11)(12) …”
Section: Sample Characteristicsmentioning
confidence: 99%
“…A recent study showed excellent psychometric properties, including internal consistency reliability and construct validity, for the Swedish parental version of the SDQ in online and paper-and-pencil versions (7). Research on the SDQ in Sweden began with a study in 1999 and is still ongoing.…”
Section: Introductionmentioning
confidence: 99%
“…Responses to each of the five peer problem items (e.g., playing alone; being bullied and generally not liked by other children) were assessed on a 3-point Likert scale (not true, somewhat true, or certainly true). The psychometric properties are well established (Bjornsdotter, Enebrink, & Ghaderi, 2013; Bourdon, Goodman, Rae, Simpson, & Koretz, 2005; Goodman, 2001). In the current study, the reliability of the peer problems subscale was adequate ( α = .74).…”
Section: Methodsmentioning
confidence: 99%